If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7w + -19 = 5w + -1x Reorder the terms: -19 + 7w = 5w + -1x Solving -19 + 7w = 5w + -1x Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. -19 + 7w + -5w = 5w + -5w + -1x Combine like terms: 7w + -5w = 2w -19 + 2w = 5w + -5w + -1x Combine like terms: 5w + -5w = 0 -19 + 2w = 0 + -1x -19 + 2w = -1x Add '19' to each side of the equation. -19 + 19 + 2w = 19 + -1x Combine like terms: -19 + 19 = 0 0 + 2w = 19 + -1x 2w = 19 + -1x Divide each side by '2'. w = 9.5 + -0.5x Simplifying w = 9.5 + -0.5x
| 4y-1+8y=-4 | | y=(3-2-4) | | -5c+10=-10+4-9c | | 5+2r=2x+6 | | X/3-1/2=1/4 | | K-13=57 | | 9(x+3)-3=29-3x-5+12x | | 7w=5w+8 | | 3/8=?/24 | | 2x-4=9x-7-7x | | 8x^2+16x+5=0 | | 2(4-6)-3(1+3x)=16 | | 3x^2-17x=-6 | | y=(3-2-4)2 | | 23+4v=83 | | e^7x*e^2=e^2x+8 | | 8x+3y=48slope | | 34x1/3= | | 4(5x+1)-12x=2(4x-2) | | -8z+31=2z | | 8x+3y=48 | | 8y+10-4y=10+3y+4 | | 1/5x+4=1/3x+2 | | 6x+6+5x+(-10)= | | 2(9x+6)=8 | | 9*x+27=-72 | | 11-q=12 | | (X+2)(X-1)=7+x | | 12=2x-3 | | 15=5+2d | | -21x=-120 | | 3(x+3)=(5x+1) |